1968
DOI: 10.1111/imj.1968.17.4.295
|View full text |Cite
|
Sign up to set email alerts
|

The Excretion of Free Noradrenaline and Adrenaline by Healthy Young Subjects and by Patients With Essential Hypertension

Abstract: SUMMARY The possible relationship between arterial pressure and the excretion of free noradrenaline and adrenaline in the urine was the subject of a study of 58 university students and 33 patients with untreated essential hypertension. The urine was collected during the morning with the subjects fasting, recumbent and undisturbed. The mean excretion rate of free noradrenaline by the students was 0.94 µg. per hour and by the hypertensives, 1.65 µg. per hour. The mean excretion rates of free adrenaline were 0.47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1969
1969
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…The fact that urinary noradrenaline excretion was not absolutely increased in any of the hypertensive subjects is in contrast to other studies, in which increased urinary noradrenaline excretion has been found in up to 25% of the hypertensive subjects studied (Nestel & Doyle, 1968;Nestel & Esler, 1970;Esler & Nestel, 1973). These studies, however, were performed in selected hospital series and the groups of normal and hypertensive subjects compared were not homogeneous for age and sex.…”
Section: Discussioncontrasting
confidence: 91%
“…The fact that urinary noradrenaline excretion was not absolutely increased in any of the hypertensive subjects is in contrast to other studies, in which increased urinary noradrenaline excretion has been found in up to 25% of the hypertensive subjects studied (Nestel & Doyle, 1968;Nestel & Esler, 1970;Esler & Nestel, 1973). These studies, however, were performed in selected hospital series and the groups of normal and hypertensive subjects compared were not homogeneous for age and sex.…”
Section: Discussioncontrasting
confidence: 91%